2012
DOI: 10.3389/fpsyg.2012.00098
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Facial Emotion Processing in Neurological and Psychiatric Conditions

Abstract: Patients suffering from various neurological and psychiatric disorders show different levels of facial emotion recognition (FER) impairment, sometimes from the early phases of the disease. Investigating the relative severity of deficits in FER across different clinical and high-risk populations has potential implications for the diagnosis and treatment of these diseases, and could also allow us to understand the neurobiological mechanisms of emotion perception itself. To investigate the role of the dopaminergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 107 publications
(139 reference statements)
3
45
0
6
Order By: Relevance
“…A similar effect is described in studies concerning aging-associated and psychiatric diseases [for a comparison with neurodegenerative disorders, see Bediou et al, 2012]. While young adults recall negative events more easily than neutral events (Negativity bias; [90], older people tend to mainly focus on positive stimuli [91] and the ability to recognize negative facial expressions declines [92][93][94].…”
Section: The Visual Discrimination Of Emotion In MCImentioning
confidence: 55%
“…A similar effect is described in studies concerning aging-associated and psychiatric diseases [for a comparison with neurodegenerative disorders, see Bediou et al, 2012]. While young adults recall negative events more easily than neutral events (Negativity bias; [90], older people tend to mainly focus on positive stimuli [91] and the ability to recognize negative facial expressions declines [92][93][94].…”
Section: The Visual Discrimination Of Emotion In MCImentioning
confidence: 55%
“…Many have questioned whether persons with PD are also impaired their ability to perceive facial expressions of emotion. The findings from individual studies have been mixed; some studies have reported impaired perception of facial expressions of emotion in PD [5][6][7]9,10,[12][13][14][15][16]22,32,34,35,38,44,47,50,51,58,59,68] whereas others have found no such impairment [2,18,20,31,45,53,60,63,65]. Despite mixed findings from individual studies, a recent meta-analysis by Gray and TickleDegnen [30] concluded that those with PD were impaired in perceiving facial expressions of emotion and that this impairment was unrelated to the ability to perceive visual form.…”
Section: Introductionmentioning
confidence: 92%
“…Perceiving the mental and emotional states of other individuals is an inevitable requirement of social relationships. In the recent years, researchers have turned their attention to the topic of social relations in IPD and begun to question to what extent would such deficits affect social functioning in IPD (18,19).…”
Section: Discussionmentioning
confidence: 99%